Role of Pseudomonas aeruginosa in Stimulating Respiratory Pro-Inflammatory Immune Response (World Journal of Experimental Biosciences, 2021)
The current study sheds light on the innate immune response as well as the inflammation that occurs as a result of the host cells being exposed to Pseudomonas aeruginosa. It also showed the role of receptors on the surface of epithelial cells or other immune cells, especially those responsible for the primary immune response and the cells that cover the mucosal canal such as the respiratory tract. The study also showed how the response to P. aeruginosa occurs at the level of the inflammatory immune response as well as the cellular immune response represented by phagocytosis that occurs by phagocytic cells (macrophages) and polymorphonuclear cells (neutrophil). The possibility of finding a vaccine against infection with P. aeruginosa was also covered in this review, as this bacterium is responsible for a high rate of mortality, especially for patients who suffer from immunosuppression.